Radial artery occlusion after transradial coronary catheterization - Avdikos, Grigorios; Karatasakis, Aris; Tsoumeleas, Andreas; Lazaris, Efstathios; Ziakas, Antonios; Koutouzis, Michael (Cardiovascular Diagnosis and Therapy; Vol 7, No 3 (June 16, 2017): Cardiovascular Diagnosis and Therapy, 2017)
The transradial approach (TRA) for coronary angiography and interventions is increasingly utilized around the world. Radial artery occlusion (RAO) is the most common significant complication after transradial catheterization, with incidence varying between 1% and 10%. Although RAO is rarely accompanied by hand ischemia, it is an important complication because it prohibits future transradial access and radial artery utilization as a conduit for coronary artery bypass grafting or arteriovenous fistula formation. In this review, we discuss factors predicting the occurrence of RAO, aspects of accurate and prompt recognition, methods that contribute to its prevention and possible treatment options.